2021
DOI: 10.20965/jdr.2021.p0588
|View full text |Cite
|
Sign up to set email alerts
|

Study on Combining Two Faster R-CNN Models for Landslide Detection with a Classification Decision Tree to Improve the Detection Performance

Abstract: This study aims to improve the accuracy of landslide detection in satellite images by combining two object detection models based on a faster region-based convolutional neural network (Faster R-CNN) with a classification decision tree. The proposed method combines the predicted results from the two Faster R-CNN models and classifies their features with a classification decision tree to generate a bounding-box that surrounds the landslide area in the input image. The first Faster R-CNN model is trained by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The authors applied it to detect geological hazards of slope failure in Huangdao District, and it only missed two landslides, demonstrating a high detection accuracy. To improve the accuracy of landslide detection in satellite images, Tanatipuknon et al (2021) [94] combined two object detection models based on Faster R-CNN with a classification decision tree (DT). In detail, the first Faster R-CNN was trained on true color (RGB) images, and the other was trained with grayscale DEMs.…”
Section: Landslide Detection (Object-based)mentioning
confidence: 99%
“…The authors applied it to detect geological hazards of slope failure in Huangdao District, and it only missed two landslides, demonstrating a high detection accuracy. To improve the accuracy of landslide detection in satellite images, Tanatipuknon et al (2021) [94] combined two object detection models based on Faster R-CNN with a classification decision tree (DT). In detail, the first Faster R-CNN was trained on true color (RGB) images, and the other was trained with grayscale DEMs.…”
Section: Landslide Detection (Object-based)mentioning
confidence: 99%
“…Liu et al [28] proposed an attention-boosted Mask-R CNN to detect landslide from InSAR deformation images. Tanatipuknon et al [29] combined the Faster-R-CNN and classification decision tree for training landslide detection model, the evaluation results showed that the combination method achieved a superior performance. Yang et al [30] proposed a backgroundenhancement Mask R-CNN method to detect landslide, the result showed that the background-enhancement significantly improved model performance.…”
Section: Introductionmentioning
confidence: 99%
“…Their model achieved high indicators in terms of accuracy and recall, showing that the image segmentation effect of the landslide area was better when using a deep neural network. Tanatipuknon et al [12] realized target detection in landslide areas based on the Faster R-CNN [13] detector, which has a higher accuracy than traditional object-oriented classification methods. Cheng et al [14] designed a lightweight target detection network based on the YOLO target detection framework, which had a high recognition accuracy while maintaining a small size.…”
Section: Introductionmentioning
confidence: 99%